Basic Statistics Relating to the Indian Economy 1950-51—1979-80 Government of India - Planning Commission (Planning Commission, 1950)
The indicators given in this table have been prepared with base 1950-51=100 by arithmetically converting the different series of Index number and from the original Statistical data Wherever data for 1950-51 are not available, base periods have been shifted to the year for which the data are available in the first instance.
Central Statistical Organisation, Department of Statistics, Ministry of Planning, Government of India